2018
DOI: 10.1021/jacs.8b10134
|View full text |Cite
|
Sign up to set email alerts
|

Total Enzyme Syntheses of Napyradiomycins A1 and B1

Abstract: The biosynthetic route to the napyradiomycin family of bacterial meroterpenoids has been fully described 32 years following their original isolation and 11 years after their gene cluster discovery. The antimicrobial and cytotoxic natural products napyradiomycins A1 and B1 are produced using three organic substrates (1,3,6,8-tetrahydroxynaphthalene, dimethylallyl pyrophosphate, and geranyl pyrophosphate), and catalysis via five enzymes: two aromatic prenyltransferases (NapT8 and T9); and three vanadium dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Vanadium-dependent haloperoxidases require vanadate and use hydrogen peroxide for halide oxidation, yielding hypohalite (HOX) intermediates chemically equivalent to an electrophilic halenium ion 'X + ' for halogenation of electron rich substrates (Butler, 1998;Butler and Carter-Franklin, 2004;Winter and Moore, 2009). Although initially described as enzymes producing hypohalous acids as diffusible halogenating agent, thereby lacking substrate specificity or regioselectivity (Itoh et al, 1988;van Pée and Patallo, 2006), recently several biosynthetic Streptomyces V-HPOs, among them NapH1, have been identified to catalyse stereoselective halogenation reactions, suggesting an enzyme-bound halenium ion rather than free hypohalous acid as the halogenating agent (Winter and Moore, 2009;McKinnie et al, 2018). These selective enzymes participate in complex biosynthetic pathways Carter-Franklin and Butler, 2004;Winter et al, 2007;Bernhardt et al, 2011;McKinnie et al, 2018).…”
Section: Vanadium-dependent Alkyl Quinolone Haloperoxidase V-hpo Hz11mentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium-dependent haloperoxidases require vanadate and use hydrogen peroxide for halide oxidation, yielding hypohalite (HOX) intermediates chemically equivalent to an electrophilic halenium ion 'X + ' for halogenation of electron rich substrates (Butler, 1998;Butler and Carter-Franklin, 2004;Winter and Moore, 2009). Although initially described as enzymes producing hypohalous acids as diffusible halogenating agent, thereby lacking substrate specificity or regioselectivity (Itoh et al, 1988;van Pée and Patallo, 2006), recently several biosynthetic Streptomyces V-HPOs, among them NapH1, have been identified to catalyse stereoselective halogenation reactions, suggesting an enzyme-bound halenium ion rather than free hypohalous acid as the halogenating agent (Winter and Moore, 2009;McKinnie et al, 2018). These selective enzymes participate in complex biosynthetic pathways Carter-Franklin and Butler, 2004;Winter et al, 2007;Bernhardt et al, 2011;McKinnie et al, 2018).…”
Section: Vanadium-dependent Alkyl Quinolone Haloperoxidase V-hpo Hz11mentioning
confidence: 99%
“…Although initially described as enzymes producing hypohalous acids as diffusible halogenating agent, thereby lacking substrate specificity or regioselectivity (Itoh et al, 1988;van Pée and Patallo, 2006), recently several biosynthetic Streptomyces V-HPOs, among them NapH1, have been identified to catalyse stereoselective halogenation reactions, suggesting an enzyme-bound halenium ion rather than free hypohalous acid as the halogenating agent (Winter and Moore, 2009;McKinnie et al, 2018). These selective enzymes participate in complex biosynthetic pathways Carter-Franklin and Butler, 2004;Winter et al, 2007;Bernhardt et al, 2011;McKinnie et al, 2018).…”
Section: Vanadium-dependent Alkyl Quinolone Haloperoxidase V-hpo Hz11mentioning
confidence: 99%
“…CNQ-525, and its analysis established the link between the presence of three vanadium-dependent haloperoxidases (VHPOs), (NapH1, NapH3, and NapH4) and a chloronium-induced meroterpene cyclization pathway [28]. The full biosynthetic route to these metabolites from three precursors (1,3,6,8-tetrahydroxynaphthalene, dimethylallyl pyrophosphate, and geranyl pyrophosphate), has been recently described and highlights the key role of those VHPO enzymes [29].…”
Section: Discussionmentioning
confidence: 98%
“…Comprehensive analysis of 1D and 2D NMR data of The relative stereochemistry of the dihydropyran ring of compound 1 (Figure 3) was assigned by interpretation of ROESY data ( Figure S7) and the coupling constants observed in its 1 H NMR spectrum (Table 1, Figure S2) in combination with molecular modelling using Chem3D 12.0 Pro. The biosynthetic route for all napyradiomycins described to date was also considered [3,28,29]. The almost equally intense ROESY correlations observed between H-3 and both geminal methyl groups (C-20 and C-21) together with a coupling constant value of 6.4 Hz between protons H-3 and H-4 ( Figure 3), in good agreement with a dihedral angle of 28.7° measured in the energy-minimized molecular model ( Figure S8), confirmed the relative configuration at C-3 of the dihydropyran ring in 1.…”
Section: Structural Elucidationmentioning
confidence: 99%
“…[97] Using a heterologous soluble expression of NapH4 in Streptomyces lividans TK23, it was shown that NapH4 is involved in the halogenation-induced cyclization of a geranyl moiety to form an exomethylene-containing chlorinated cyclohexane ring of napyradiomycin B1. [98] Though napH3 has above 50% sequence identity with NapH1 and napH4, the recombinant NapH3 enzyme exhibited no halogenation activity. Instead, it mediated the C4-to-C3 α-hydroxyketone rearrangement of the geranyl moiety with synthetic and pathway intermediate to form naphthomevalin 11.…”
Section: Reconstructed Biosynthetic and Natural Product Pathways Withmentioning
confidence: 95%